Intercellular contractile force attenuates chemosensitivity through Notch-MVP-mediated nuclear drug export - Pengyu Du; Kai Tang; Xi Chen; Ying Xin; Bin Hu; Jianfeng Meng; Guanshuo Hu; Cunyu Zhang; Keming Li; Youhua Tan (Proceedings of the National Academy of Sciences, 2025)
Resistance to chemotherapeutics is one major challenge to clinical effectiveness of cancer treatment and is primarily interpreted by various biochemical mechanisms. This study establishes an inverse correlation between tumor cell contractility and chemosensitivity. In both clinical biopsies and cancer cell lines, high/low actomyosin-mediated contractile force attenuates/enhances the vulnerability to chemotherapy, which depends on intercellular force propagation. Cell–cell interaction force activates the mechanosensitive Notch signaling that upregulates the downstream effector major vault protein, which facilitates the export of chemotherapy drugs from nuclei, leading to the reduction of chemosensitivity. Cellular contractility promotes the tolerance of tumor xenografts to chemotherapy and sustains tumor growth in vivo, which can be reversed by the inhibition of contractile force, Notch signaling, or major vault protein. Further, the actomyosin-Notch signaling is associated with drug resistance and cancer recurrence of patients. These findings unveil a regulatory role of intercellular force in chemosensitivity, which could be harnessed as a promising target for cancer mechanotherapeutics.